Harta dan kepemilikan dalam ekonomi Islam: Keseimbangan antara individu dan masyarakat - sigit, hilmy zhaffran (Maliki Interdisciplinary Journal, 2025)
Islamic economics, as a system based on sharia, regulates financial aspects while providing moral guidance in wealth management. The concept of ownership in Islamic economics is understood as a trust that must be managed for the welfare of society. With the emergence of global challenges such as economic inequality, a deep understanding of wealth and ownership concepts in Islamic economics becomes increasingly relevant. This article discusses the definition of wealth, its sources and roles, as well as the principles of ownership and wealth distribution in a modern context. It is hoped that the application of sharia principles can help create a fairer and more prosperous society. Understanding the concept of wealth and ownership in Islamic economics is very important, especially amidst the challenges faced by modern society today. Wealth, in the view of Islam, is not just a tool to fulfill personal needs, but also a trust that must be managed well for the collective interest.